Connected 24 hours in the global economy - Altman, Daniel (Farrar, Straus and Giroux, 2008)
In Connected: 24 Hours in the Global Economy, journalist and economist Daniel Altman answers this question by visiting more than a dozen cities around the world and tracing the threads of our ever-changing, ever-integrating economic fabric. Readers travel to Syria, where the president wants to launch his country's first stock market; to Brazil, where a corruption scandal is brushed under the rug in the name of economic stability; to East Timor, where a new nation grapples with its impending oil wealth. Altman diagrams all the gears and cogs, showing how they fit together in the vast machinery of the global economy--all in the events of a single day. Connected: 24 Hours in the Global Economy is a new and accessible way to look at our complex world.